Determinants of Tax Avoidance: The Effects of Narrative Disclosure, Profitability, Leverage, and Firm Size - Rizaul Alda; Risya Khaerun Nisa; Wuryaningsih Wuryaningsih (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2026)
Purpose: This study aims to examine the effect of narrative disclosure, profitability, leverage, and firm size on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange during 2020–2024. Method: This study uses data from energy sector companies selected through purposive sampling. Narrative disclosure is measured using sentiment analysis based on the Loughran–McDonald dictionary with R Studio, and analyzed using panel data regression with EViews 13 Results: The results show that narrative disclosure and leverage have a negative and significant effect on tax avoidance. Meanwhile, profitability and firm size have no effect on the dependent variable.. Implications: This study highlights the importance of transparency in narrative disclosure to reduce tax avoidance and provides insights for regulators to improve corporate reporting quality Novelty: This study integrates sentiment analysis of narrative disclosure into tax avoidance research in the energy sector, which remains underexplored in Indonesia.